Due date [videorecording (DVD)] - Phillips, Todd, 1970-; Phillips, Todd, 1970-; Phillips, Todd, 1970-; Downey, Robert, Jr., 1965-; Galifianakis, Zach; Monaghan, Michelle; Lewis, Juliette; RZA (Rapper); Foxx, Jamie (Warner Home Video, 2011)
"Expectant first-time father Peter Highman (Robert Downey, Jr.) looks forward to his new child's due date five days away. As Peter hurries to catch a flight home from Atlanta to be at his wife's side for the birth, his best intentions go completely awry when an encounter with aspiring actor Ethan Tremblay (Zach Galifianakis) forces Peter to hitch a ride with Ethan on a cross-country trip that will ultimately destroy several cars, many friendships and Peter's last nerve"--Container.